Olhares pós-coloniais: Lisboa, São Paulo e relações étnico-raciais. Em tempos de globalização, desigualdade, diferença, racismo e anti-racismo - Fernandes, José Antonio da Costa (2006)
This thesis accomplished a comparative analysis on the social and ethnic-racial relationships which occur in Brazil and Portugal, with priority in the cities of Sao Paulo and Lisbon in the globalization process, in order to identify how social inequalities happen, racism and the ways by which it is faced, into the perspective of some social movements counter-hegemony. It was necessary to retrieve the recent Histories of the two countries, emphasizing a social History in what the ethnic-racial matter was of paramount importance. During the analysis of the two countries globalization process it was stood out differences and similarities between them, mainly in these cities, which were chosen for he fact of being considered global, headquarters of the selected social movements used in this study and because social strain in these cities is quite sharp. These social movements were evaluated considering their linkage to the regulation field (maintenance of the global neo-liberal order) and to the social emancipation (rupture and building of altematives). Public policies towards struggling racial discriminationwere analyzed and compared in both countries. Starting ITom the analysis of the factors which affected racism and inequality in both cities, post-colonialism and the building of solidarities due to these relationshipswere evaluated